Navigating challenges in the management of Dactylopius opuntiae (Cockerell): Transitioning from ’introduction biological control’ to a preemptive strategy of artificial seeding of a natural enemy - Zvi Mendel; Alexei Protasov; Omer Golan; Daniel Bensimon; Oren Kolodny; Pompeo Suma (Biological Control)
The invasion of false carmine cochineal Dactylopius opuntiae (Cockerell) (Hemiptera; Dactylopiidae) in the Mediterranean region presents a serious threat to cactus pear cultivation. The cochineal was first identified in Israel in 2013, and it soon became clear that biological control is the only long-term solution to protect the cactus pear Opuntia ficus-indica. Releases of the introduced predatory beetle Hyperaspis trifurcata Schaeffer (Coleoptera; Coccinellidae) began in 2016, demonstrating high efficacy and leading to a decline in cochineal populations and plant survival. While H. trifurcata can autonomously reach new cochineal hotspots, it often arrives too late to prevent substantial damage to cactus pear. Human intervention is therefore necessary to expedite the predator’s establishment in new infested sites. To facilitate the spread of the beetle, we consider two approaches: transferring beetle seeding stocks from northern locations through a volunteer network organized by the research team, and applying the ’predator – prey dual introduction’ concept to preemptively mitigate new hotspots expected to emerge as the cochineal spreads southward via winds or birds. These activities have led to a major decrease in the rate of spread of the cochineal population in the East Mediterranean, and in the damage that it inflicts to cactus pear hedgerows. Implementing a similar approach in North Africa can prevent or slow the spread of the cochineal to the northern coast of the central Mediterranean and avoid the heavy damage experienced in Morocco.